2004
DOI: 10.1109/tr.2004.823849
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Fault Trees for Advanced Process Control Systems—Application to Cascade Control Loops

Abstract: A systematic approach to construct fault trees for advanced process control systems is presented in this paper. For illustration purpose, the proposed method is explained with a specific feedback scheme, i.e., the cascade control strategy. The digraph configuration of a standard system is first described and analyzed in detail. On the basis of a series of qualitative simulation studies, all failure mechanisms can be identified and summarized with a set of generalized fault-tree structures. The fault trees prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…FT originally developed at Bell Lab in 1960s is a logic cause-effect tree that propagates primary events (faults) from bottom to the top level events (symptoms). A recent application of FTs in FDD was reported in [57] for reliability analysis and fault diagnosis. SGD is a graph with directed arcs leading from a 'cause' node to 'effect' nodes and these arcs are given a positive or negative sign.…”
Section: Artificial Intelligence and Machine Learning In Fddmentioning
confidence: 99%
“…FT originally developed at Bell Lab in 1960s is a logic cause-effect tree that propagates primary events (faults) from bottom to the top level events (symptoms). A recent application of FTs in FDD was reported in [57] for reliability analysis and fault diagnosis. SGD is a graph with directed arcs leading from a 'cause' node to 'effect' nodes and these arcs are given a positive or negative sign.…”
Section: Artificial Intelligence and Machine Learning In Fddmentioning
confidence: 99%
“…Thus, the complete fault propagation process in a NFBL is often described on a case-by-case basis. 30 However, if the NFBL in Figure 1c is a control loop, then the final steady-state values of the loop variables can be assigned according to the general guidelines suggested by Ju et al 32 Table 1 is a listing of the final states of control NFBLs in various scenarios. Thus, the FPP corresponding to D X (+1) in this situation can be expressed as It can be observed that the final states of all loop variables in this FPP are lumped into a single ending node in a square bracket and their precedence order is left unspecified.…”
Section: Fault Propagation Pathsmentioning
confidence: 99%
“…Let us assume that the combined effects of m 2 (-1) and m 3 (+1) are equivalent to those caused by an uncontrollable disturbance. Consequently, the final states of loop variables can be assigned by following the approach suggested in the work of Ju et al, 24 i.e., h(+1), s 5 (+1), s 6 (-10), and m 1 (-10). The corresponding simulation results are shown in Figure 10a.…”
Section: Case Studiesmentioning
confidence: 99%